The Pre-transition Experiences of Parents of Pupils with Additional Needs Moving from Primary to Post-primary School in an Area of Social Disadvantage in Ireland - Dupont, Maeve; Scanlon, Geraldine; Doyle, Alison; Kenny, Neil; Flynn, Paula (International Journal of Educational and Life Transitions, 2023)
This paper explores the pre-transition preparation experiences of parents of 6th class children from two single sex primary schools in an area of social disadvantage in the Republic of Ireland. The findings are taken from a larger commissioned feasibility study that examined the perspectives of a number of stakeholders in primary and post primary schools (in the same area) to identify a model of support that is required for students with additional needs to make a seamless and sustainable transition from primary to post- primary school. The study was conducted within The Five Bridges of Transition framework (Galton, et al., 1999), which was chosen because of its specific relevance to the transition of pupils from primary to secondary education. During Spring 2018, ten parents of male and female 6th class primary pupils were interviewed. Data was analysed using content and thematic analysis. The findings revealed that parents were very conscious of the social, emotional and curricular challenges their child might encounter at second level. However, they were not included as co-experts in the transition process and hence were largely unaware of: pupil information that was transferred from school to school; homework practices, streaming and assessment polices; available resources and support; subject choices; and curricular provision. Parents were found to require significant levels of support and guidance in navigating admissions procedures and the delay in confirming school places also added to parental anxiety, particularly for parents of children with special educational needs. Theoretical and practical implications of the findings are discussed.